Let's take a giant leap with rocket science - Abd Razak, Dzulkifli (2009)
IT was a day to be remembered, July 21, 1969, the day man first set foot on the moon. At precisely 2017 GMT, on July 20, the lunar module, named The Eagle descended on the Sea of Tranquility. At 0256 GMT the next day, astronaut Neil Armstrong stepped out of the lunar module and uttered the immortal words: "That's one small step for man, one giant leap for mankind." Together with Edwin Aldrin, Armstrong spent some 21/2 hours on the moon carrying out experiments and collecting samples, while Michael Collins orbited above in the spaceship Columbia.